The association between hematological markers of inflammation and chronic cannabis use: a systematic review and meta-analysis of observational studies - Moshfeghinia, Reza; Najibi, Amirhossein; Moradi, Mehrnaz; Assadian, Kasra; Ahmadi, Jamshid (Frontiers in Psychiatry, 2024)
Introduction: Cannabinoids, both natural and synthetic, are a subject of scientific interest. Cannabis is widely used, and its impact on health and the immune system is being studied. The endocannabinoid system influences inflammation, including the Neutrophil-to-Lymphocyte Ratio (NLR), a potential diagnostic tool. Our study investigates the connection between cannabis use and NLR. Methods: Our systematic review was registered in Prospero (#CRD42023463539). We searched six databases (PubMed, Scopus, Embase, PsycINFO, Web of Science, and CINAHL Complete) for records in English from inception to May 2024. We included observational studies that measured the Neutrophil-to-Lymphocyte Ratio (NLR) in cannabis users and control participants. We used the Newcastle-Ottawa Quality Assessment Scale to assess the quality of the included studies. We selected a random-effects model, and the statistical analysis was performed using Stata software version 17.Results: Out of a total of 4,054 records, only five articles were selected for inclusion in the metaanalysis. All of these chosen studies utilized a retrospective design. Furthermore, it's worth noting that all of the studies included were of high quality. In five studies involving 3,359 cannabis users and 10,437 non-users, no significant difference in NLR was found (WMD: 0.12 [-0.16, 0.41], I2: 39.89%).Subgroup analysis on healthy and schizophrenia participants didn't show significant NLR differences (p=0.76). Secondary analysis revealed cannabis users had higher Platelet-to-Lymphocyte Ratio (PLR) (67.80 [44.54, 91.06]), neutrophil count (0.68 [0.25, 1.12]), white blood cell count (0.92 [0.43, 1.41]), monocyte count (0.11 [0.05, 0.16]), and Systemic Immune Inflammation Index (SII) (83.48 [5.92, 157.04]) compared to non-users Conclusion: Our systematic review and meta-analysis reveal that cannabis use may affect NLR and hematologic parameters, suggesting a potential immune impact. Complex associations exist, requiring further research. Schizophrenia and pro-inflammatory factors are discussed, highlighting the need for ongoing investigation into cannabis-related immune changes and mental health.